On new mechanisms for the formation of technological superiority in modern conditions of innovative development - OSTROVSKAYA A.A.; STRENALYUK V.V.; SEMENOV A.S. (The journal of contemporary issues in business and government, 2020)
The study of trends in the development of the world economy showed the importance of innovations. In modern conditions of increasing competition in the high-tech markets, the role of management approaches and mechanisms used by players in these markets for a successful competitive struggle is increasing. The methods and approaches developed in the framework of strategic marketing have not lost their relevance at the present time. This paper shows the principal approach to reach the excellence in innovation development. World experience is presented in this work in the way to search the solution. Outsourcing approach is shown as a primary method of technology advance achievement.